The Fiskenæsset Complex, West Greenland. Part I. A Preliminary Study of the Stratigraphy, Petrology, and Whole Rock Chemistry from Qeqertarssuatsiaq. - Windley, B. F.; Herd, R. K.; Bowden, A. A. (Meddelelser om Grønland, 1973)
The Fiskenæsset complex, which occurs as conformable layers up to 1.5 km thick in high grade Early Archaean gneisses, has a well-preserved igneous stratigraphy. An upward sequence of lithological zones is observed in the complex as follows: 1. Pyroxene Amphibolite; 2. Ultramafic Group (hornblende-bearing spinel- and magnetite-layered dunites, peridotites, pyroxenites); 3. Layered leuco-gabbro; 4. Dark gabbro; 5. Homogeneous leuco-gabbro; 6. Anorthosite; 7. Chromite horizon; 8. Garnet Anorthosite; 9. Pyroxene Amphibolite. Eighteen whole rock XRF analyses (for major and trace elements) indicate that this sequence is mainly the differentiation product of a basaltic magma. Cryptic layering is present within zones 2 to 8 inclusive, and shows that this part of the sequence belongs to a stratiform igneous intrusion, zone 8 being the topmost layer of the original igneous stratigraphy. There is especially a marked upward increase in the Fe/Mg ratio. The amphibolites of zones 1 and 9 are much richer in iron than any rocks belonging to the intrusion, and are considered to have been volcanics into which it was emplaced. Metasomatic sapphirine-rich rocks are localised along the contact of zones 8 and 9. The complex has internal sub-complexes within which its upper zones are locally confined. The stratigraphic sequence is repeated symmetrically in reverse order and the differentiation trends of the two halves mirror each other. The original body was flattened so that its layering was deformed into an isoclinal syncline. This deformation accounts for the repeated stratigraphy. The complex was subsequently double folded and metamorphosed under both granulite and amphibolite facies conditions. Mineral assemblages indicate that there may have been appreciable water in the original magma, and this viewpoint is strengthened by the observed differentiation trend.